Cancer biomarkers in human atherosclerotic lesions: detection of DNA adducts - Izzotti, Alberto; De Flora, S.; Petrilli, G. L.; Gallagher, J.; Rojas, M.; Alexandrov, K.; Bartsch, Helmut; Lewtas, J. (Cancer epidemiology, biomarkers & prevention, 1995)
Since somatic mutations are suspected to contribute to the pathogenesis not only of cancer but also of atherosclerotic plaques, we measured DNA adducts in the smooth muscle layer of atherosclerotic lesions in abdominal aorta specimens taken at surgery from seven patients. DNA adducts were evaluated in three laboratories by means of different molecular dosimetry methods, including: (a) HPLC/fluorescence, which specifically identifies the DNA adducts of the anti-benzo(a)pyrene (BPDE) isomer; (b) two- and three-dimensional synchronous fluorescence spectrophotometries, which detect DNA adducts of BPDE and other reactive metabolites of polycyclic aromatic hydrocarbons; and (c) 32P postlabeling, which reveals the presence of a variety of types of DNA adducts. The HPLC/fluorescence method provided for the first time evidence for the presence of BPDE-DNA specific adducts in three of six specimens tested. Synchronous fluorescence spectrophotometry displayed broad areas of fluorescence in all seven specimens, thereby suggesting the occurrence not only of BDPE-DNA but also of other DNA adducts with similar fluorescence characteristics. All specimens were also positive at 32P postlabeling, which revealed multiple spots detectable following enrichment either with nuclease P1 or butanol, indicative of the presence of different aromatic DNA adducts. Thus, the data obtained by applying typical cancer biomarkers provide further support to the hypothesis that there may be similarities between the carcinogenic and the atherogenic processes, and in particular that genetic alterations caused by DNA-binding agents in the artery wall may be detected in atherosclerotic lesions.